Exploring the Intersection of TPACK and Professional Competence: A Study on Differentiated Instruction Development within Indonesia’s Merdeka Curriculum - Varisa Tri Utari; Ika Maryani; Enung Hasanah; Suyatno Suyatno; Asih Mardati; Norma Bastian; Amir Karimi; Mark Angelo C Reotutor (Indonesian Journal on Learning and Advanced Education (IJOLAE), 2025)
Despite the growing emphasis on differentiated instruction in modern education, there remains a noticeable gap in research examining the integration of Technological, Pedagogical, and Content Knowledge (TPACK) with professional competence, particularly within the context of Indonesia's Merdeka Curriculum. This study aims to assess teachers' levels of TPACK and professional competence in developing differentiated instruction in Yogyakarta, Indonesia, while exploring the correlation between these two variables. Adopting a quantitative correlational research design, the study employed stratified random sampling to select a sample of 84 teachers from eight elementary schools currently implementing the Merdeka Curriculum (Independent Learning Curriculum). Descriptive statistics and hypothesis testing, using the Spearman-Brown formula, were utilized for data analysis. The findings indicate that the participating teachers exhibit moderate levels of both TPACK and professional competence in developing differentiated instruction. Moreover, hypothesis testing revealed a strong and significant correlation between teachers' TPACK and their professional competence in designing differentiated instruction. This research highlights the importance for teacher training institutions to prioritize the development of TPACK, enabling educators to effectively adapt to evolving educational policies.